Implementación de un sistema basado en minería de datos para la obtención de las preferencias estudiantiles de nivel superíor para la planificación de materias - Altamirano, M. (2009)
In the area of upgrading the living being and academic records need to obtain a student preferences with regard to good planning matters. This paper analyzes and after seeing the need for student university uses the discriminant models for the development of ranking of preferences, it is defined in the datamartswhere are the operational data, facts and values knowledge extracted from the electronic questionnaires. Moreover implement a Web interface to: data entry of students, datamarts the operation and decision-making environment.